2005
DOI: 10.1021/jf040130h
|View full text |Cite
|
Sign up to set email alerts
|

Some Chemical Composition and Biological Activity of Northern Argentine Propolis

Abstract: Twenty-five samples of propolis were collected from seven different regions in northern Argentina; ethanolic extracts of propolis were prepared from all samples, and the respective samples were examined for UV absorption spectra, RPHPTLC, RPHPLC, antimicrobial activity, antiradical activity, and total phenolic content. It was found that 16 of the 25 samples showed a phenolic profile similar to that found in samples from southern Brazil and corresponding to poplar-based propolis and that the rest of the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 19 publications
(32 reference statements)
4
55
2
9
Order By: Relevance
“…Among studies that have been carried out on phenolic compounds found in other propolis samples of different origin, in an investigation carried out by Christov et al [53] on Canadian propolis, cinnamic acid determined in the chemical composition which was also determined to exist in cinnamic acid derivative form in the propolis sample used in the present study, was demonstrated to exhibit strong radical scavenging activity. Furthermore, in a study carried out by Isla et al [54] on the antioxidant effect of Argentine propolis, the total phenolic compounds present in the composition of propolis were underlined to display strong radical scavenging effect. In an investigation conducted by Nakajima et al [55] have determined the derivatives of caffeoylquinic acid and cinnamic acid, found in Brazilian propolis, to exhibit antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies that have been carried out on phenolic compounds found in other propolis samples of different origin, in an investigation carried out by Christov et al [53] on Canadian propolis, cinnamic acid determined in the chemical composition which was also determined to exist in cinnamic acid derivative form in the propolis sample used in the present study, was demonstrated to exhibit strong radical scavenging activity. Furthermore, in a study carried out by Isla et al [54] on the antioxidant effect of Argentine propolis, the total phenolic compounds present in the composition of propolis were underlined to display strong radical scavenging effect. In an investigation conducted by Nakajima et al [55] have determined the derivatives of caffeoylquinic acid and cinnamic acid, found in Brazilian propolis, to exhibit antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro experiments have revealed that propolis could synergize the effect of selected antibiotics (Kedzia and Holderna, 1986;Krol et al, 1993;Scheller et al, 1999;Stepanovic et al, 2003;Fernandes Jr et al, 2005;Scazzocchio et al, 2006). Despite the fact that numerous studies have been published on the antimicrobial activity of propolis from temperate and tropical regions, previous investigations have been limited mainly to samples obtained from either one area, different locations within one country (Kartal et al, 2003;Stepanovic et al, 2003;Uzel et al, 2005;Hayacibara et al, 2005;Popova et al, 2005;Lu et al, 2005;Isla et al, 2005) or on samples collected within the same region by different honeybee races (Fernandes Jr et al, 2001;Silici and Kutluca, 2005;. Comparative biological studies of propolis of different provenance and chemical composition, although important in helping to decide on the best formulation to be used in therapy, are rather limited (Bankova, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…aromatic acids and esters and (ii) samples from tropical areas, devoid or containing traces of poplar constituents but rich in other metabolites (Burdock, 1998;Bankova, 2005a;Isla et al, 2005;Orsi et al, 2005). Propolis has a long history of use in traditional medicine and is a natural remedy found today in many health-food stores (Burdock, 1998).…”
mentioning
confidence: 99%
“…The advantages of this spectrophotometric method are its simplicity, good repeatability, and acceptable accuracy. In previous reports (Isla et al, 2001(Isla et al, , 2005(Isla et al, , 2012aNieva et al, 2005;Ordoñez et al, 2011;Vera et al, 2011;Solórzano et al, 2012), a wide range of phenolic compound concentrations in propolis samples from different phytogeographical provinces of Argentine (Isla et al, 2012b) have been described.…”
Section: Resultsmentioning
confidence: 92%
“…Argentine propolis has been used extensively in folk medicine since it possesses antifungal, antibacterial, anti-inflammatory, and antioxidant properties among others (Isla et al, 2001(Isla et al, , 2005(Isla et al, , 2009(Isla et al, , 2012aOrdóñez et al, 2011;Solórzano et al, 2012;Vera et al, 2011). Bee glue chemical composition depends on the local flora and geographic and climatic characteristics of the collection site (Bankova et al, 2006;Choi et al, 2006;Isla et al, 2009Isla et al, , 2012aSolórzano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%